Pengaruh Variasi Gen CYP2D6 Terhadap Terapi Tamoxifen Pada Pasien Kanker Payudara di Kawasan Asia - Septi, Annisa Frastica; Zahra, Aliya Azkia; Malau, Jekmal (STIKES Ngesti Waluyo, 2024)
reast cancer is one of the most prevalent cancers in society, especially among women. Tamoxifen is often used as a first-line therapy for breast cancer and reduces the risk of recurrence in ER+ breast cancer. However, the response to treatment varies due to genetic variability resulting from polymorphisms in the DNA encoding drug-metabolism enzymes, including the CYP2D6 gene. This literature review aimed to evaluate the impact of CYP2D6 gene variants on the effectiveness of tamoxifen in breast cancer treatment. A literature search was conducted through PubMed, Google Scholar, and BMC Cancer using relevant keywords. The selected articles were no more than ten years old (2014-2024), with criteria for inclusion and exclusion. The review of articles from various research journals found that in the Asian region, the CYP2D6 gene variant allele *10 was most frequently seen, resulting in Intermediate Metabolism (IM) in tamoxifen therapy. Patients with IM metabolism tend to have suboptimal therapeutic responses and require tamoxifen dose adjustments.Conversely, patients with Normal Metabolism (NM/EM) tend to have better therapeutic responses. Genetic variability in the CYP2D6 gene affects the activity of the CYP2D6 enzyme, which functions to convert tamoxifen into its active form, Endoxifen. Some individuals may have low (Poor Metabolizer), Intermediate (Intermediate Metabolizer), Normal (Extensive Metabolizer), or even high (Ultra-rapid Metabolizer) enzyme activity. Therefore, adjusting tamoxifen therapy based on patient genetic information is essential for optimal treatment, especially in Asia, where the CYP2D6 gene variant allele *10 is most commonly found, resulting in IM metabolism